A female economy women's work in a prairie province, 1870 - 1970 - Kinnear, Mary (McGill-Queen's Univ. Press, 1998)
"A Female Economy analyses a hundred years of women's work in Manitoba from the province's entry into Confederation in 1870 to the publication of the Report of the Royal Commission on the Status of Women in 1970. Mary Kinnear shows that women's work, whether unpaid in the household or on the farm or for wages in the industrial, service, and professional sectors, was undervalued." "While women's own views furnish the main theme, A Female Economy contributes to a developing debate in feminist economics. By focusing on women's experiences in the sexually segregated economy of a Canadian province at the geographic centre of Canada, Kinnear furnishes a paradigm for women's economic activity in most Western industrializing societies at the time."--BOOK JACKET.